Renda Per Capita não monetária: proposta metodológica aplicada à Comunidade Quilombola do Mandira - José Mariano Caccia Gouveia; Jurandyr Luciano Sanches Ross (Confins)
In order to measure and evaluate the degree of economic development, several indices have been developed and, among those universally used, the most relevant are: GDP - Gross Domestic Product, GNP - Gross National Product, HDI - Human Development Index and PCI - Per Capita Income. The latter deserves special attention once it is an isolated indicator, accounts for one third of the values ​​obtained for the HDI, nearly all GDP of the communities, in addition to being an indicator of the economic dimension of tools to measure sustainability. However, PCI induces misunderstandings in the interpretation of results once is exclusively based on monetary values that are ​​measured by work or by trade, being ineffective when applied to communities in which prevailing autonomous relations of production / consumption / commercialization. When part of the resources needed for survival is extracted from the environment or locally produced, there is no disbursement of monetary values ​​to their satisfaction, although this is also a result of performed work and therefore should be considered for calculation of IPC. In that sense, this paper presents - through a case study - the proposition, in exploratory methodology that seeks overcome this deficiency of the index. The search attempted to measure the volume of those resources and, always it was possible, assign them a monetary value, allowing obtaining an equivalent rate to the IPC, with greater consistency for application in rural communities or groups. For that rate it is suggested the name "A-PCI - Aggregated Per Capita Income," which is the sum of the IPC with non-monetary income that was possible to estimate the amount. As a result - considering only those items whose valuation was possible - this corresponded to an increase of 77.01% in local income. This new index also allows shed new perspectives on studies about "Quality of Life" and comparative analysis between urban and rural areas.